The Association of Equity, Accessibility, and Price With Primary Healthcare User's Satisfaction. (February 2014) - Lobo, Alexandrina; Duarte, Paulo; Carvalho, Amâncio; Rodrigues, Vitor; Monteiro, Maria João; Alves, Helena
The assessment of user satisfaction, and the knowledge of what factors influence satisfaction are very important for the improvement of services' quality provided. This study aims to evaluate user satisfaction with primary healthcare services. A sample of 6, 113 healthcare services users was interviewed to evaluate satisfaction and determine a global satisfaction index using a Partial Least Squares Path Model. The global user satisfaction index with healthcare centers is 58.4 points on a 100-point scale, showing that users are only moderately satisfied with the service provided. The results show that the medical care and the price of services are the main predictors of user satisfaction. Other factors such as the perception of health equity and nursing services also seem to be important contributors to satisfaction. A more disturbing result is the negative relationship between perceived accessibility and satisfaction, which requires further research.